Peran dan Fungsi Pos Bantuan Hukum (Posbakum) Pada Pengadilan Agama Biak Kelas IIB - Iryana Anwar; Muslim Lobubun (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2021)
This study aims to examine the role and function of the legal aid post (Posbakum) at Biak’s Religious Court Class IIB according to the the national supreme court decree Number 1 of 2014. This study took place at Biak’s Religious Court. The study used an empirical juridical approach. Data were collected through field observations and interviews with research respondents. Data analysis was carried out in a qualitative descriptive manner. The results showed that the implementation of the legal aid post at Biak’s Religious Court in providing services for the poor in general had been carried out very well according to the national supreme court decree Number 1 of 2014, but the community still had difficulties because of the unavailability of direct assistance by officers. it is feared that those who receive legal services will fall into the category of those who are financially able to pay for an advocate given that there are no regulations that stipulate the restriction or criteria for people who are financially incapable of paying for advocate services. This research is expected to provide information for the people of Biak in particular, and people outside Biak in general regarding the benefits of legal aid services for the lower-class community.